Influencia del PDO y ENSO en el crecimiento de siete especies forestales al sur de Ecuador - Zúñiga Sarango, Wilson Leopoldo (2023)
Climate change generates very significant impacts on terrestrial ecosystems, altering the functionality and development of species, due to modifications in climatic patterns over long periods of time, which is currently highly linked to human activities. In this study we used dendrochronological data provided by the dendrochronology laboratory of the UNL and global data from PDO and oceanic indices ENSO 1+2 and ENSO 3.4 to evaluate the influence of established phenomena on the growth of seven forest species located in five localities in the province of Loja, two localities in the province of Zamora Chinchipe and one locality in the province of Pastaza, which was used as an indicator locality. The influence was evaluated through a Pearson correlation test and three non-parametric models (GLM, GAM, GAM (REML)), with a previous elimination of trend by tree age with the Detrending method. It was found that PDO only influences the growth of species located in the Andean region in the upper middle zone of the andean mountain range, ENSO 1+2 strongly influences the growth of species located in the Pacific region in the lower zone of the western andean mountain range in dry forest, on the other hand, ENSO 3.4 only strongly influences the growth of species located in the Amazon region in the lower and lower middle zone of the andean mountain range. In conclusion, PDO and ENSO do influence the growth of forest species in southern Ecuador, but their influence will depend on the location of the species and, in the case of ENSO, the oceanic index used. Keywords: Climate change, Pacific decadal oscillations, El Niño-Southern Oscillations, Ecosystem functionality, Dendrochronology, Climate patterns.